Advanced Organic Electrode Materials for Rechargeable Sodium‐Ion Batteries. Issue 8 (20th December 2016) - Zhao, Qing; Lu, Yong; Chen, Jun
Abstract : Benefiting from the high abundance and low cost of sodium resource, rechargeable sodium‐ion batteries (SIBs) are regarded as promising candidates for large‐scale electrochemical energy storage and conversion. Due to the heavier mass and larger radius of Na + than that of Li +, SIBs with inorganic electrode materials are currently plagued with low capacity and insufficient cycling life. In comparison, organic electrode materials display the advantages of structure designability, high capacity and low limitation of cationic radius. However, organic electrode materials also encounter issues such as high‐solubility in electrolyte and low conductivity. Here, recently reported organic electrode materials, which mainly include the reactions based on either carbon‐oxygen double bond or carbon‐nitrogen double bond, and doping reactions, are systematically reviewed. Furthermore, the design strategies of organic electrodes are comprehensively summarized. The working voltage is regulated through controlling the lowest unoccupied molecular orbital energies. The theoretical capacity can be enhanced by increasing the active groups. The dissolution is inhibited with elevating the intermolecular forces with proper molecular weight. The conductivity can be improved with extending conjugated structures. Future research into organic electrodes should focus on the development of full SIBs with aqueous/aprotic electrolytes and long cycling stability. Abstract : Organic electrode materials are considered as proper selection for sodium‐ion batteries owing to their structure designability, high capacity, and low limitation of cationic radius. The recently reported organic electrode materials based on the CO bond, doping, and CN bond reactions are systematically overviewed, which provides an unambiguous understanding of working principles, design strategies and prospects of this area.